Blood parasites in northern goshawk (Accipiter gentilis) with an emphasis to Leucocytozoon toddi - Hanel, Jan; Doležalová, Jana; Stehlíková, Šárka; Modrý, David; Chudoba, Josef; Synek, Petr; Votýpka, Jan (Parasitology research, 2016)
Haemosporidians and trypanosomes of the northern goshawk (Accipiter gentilis) population in the Czech Republic were studied by morphological and molecular methods. Despite the wide distribution of these medium-large birds of prey, virtually nothing is known about their blood parasites. During a 5-year period, altogether 88 nestlings and 15 adults were screened for haemosporidians and trypanosomes by microscopic examination of blood smears and by nested PCR. Both methods revealed consistently higher prevalence of blood protists in adults, Leucocytozoon (80.0 % in adults vs. 13.6 % in nestlings), Haemoproteus (60.0 vs. 2.3 %), Plasmodium (6.7 vs. 0 %), and Trypanosoma (60.0 vs. 2.3 %). Altogether, five haemosporidian lineages were detected by cytochrome b sequencing. Two broadly distributed and host nonspecific lineages, Plasmodium (TURDUS1) and Leucocytozoon (BT2), were detected only sporadically, while three newly described northern goshawk host-specific Leucocytozoon lineages (ACGE01-03) represent the absolute majority of the haemosporidians identified by molecular methods. Our findings support evidences that in falconiform birds the Leucocytozoon toddi group is formed by several host-specific clusters, with Leucocytozoon buteonis in buzzards and Leucocytozoon mathisi in hawks. Between-year comparisons revealed that the infection status of adults remained predominantly unchanged and individuals stayed uninfected or possessed the same parasite lineages; however, two gains and one loss of blood parasite taxa were also recorded.
Keywords: Trypanosomiasis; Parasitemia; Haemosporida; Prevalence; Birds of prey; trypanozomiáza; cytochromy b; Sequence Alignment; Falconiformes; Česká republika; polymerázová řetězová reakce; Polymerase Chain Reaction; Cytochromes b; mužské pohlaví; prevalence; PCR detection; Bird Diseases; protozoální infekce zvířat; Czech Republic; Protozoan Infections, Animal; protozoální DNA; ženské pohlaví; parazitemie; nemoci ptáků; zvířata; Raptors; Host Specificity; malárie ptačí; Plasmodium; fylogeneze; Avian blood parasites; Mixed infection; Malaria, Avian; DNA, Protozoan; Trypanosoma; Female; Phylogeny; sekvenční seřazení; hostitelská specificita; Male; Animals